Effect of cenobamate on the single‐dose pharmacokinetics of multiple cytochrome P450 probes using a cocktail approach in healthy subjects - Stephen A. Greene; Charles Kwak; Marc Kamin; Laurent Vernillet; Kelli J. Glenn; Lana Gabriel; Hong Wook Kim (Wiley, 2022)
Abstract This study was designed to evaluate the effects of cenobamate, an antiseizure medication for focal seizures, on the pharmacokinetics of cytochrome P450 probes (bupropion, CYP2B6; midazolam, CYP3A4/5; warfarin, CYP2C9; and omeprazole, CYP2C19) in healthy subjects. Probes were administered alone on days 1 (bupropion) and 7 (midazolam/warfarin/omeprazole), and with cenobamate 100 mg/day on day 69 (midazolam) and cenobamate 200 mg/day on days 99 (bupropion) and 105 (midazolam/warfarin/omeprazole). No significant interaction was concluded if 90% confidence intervals (CIs) for geometric mean ratios (GMRs) for area under the curve (AUC) and maximum concentration of CYP substrates and/or their metabolites were within the no‐effect interval (0.80-1.25). When co‐administered with cenobamate 100 mg/day, AUC from time of administration up to the time of the last quantifiable concentration (AUC0-last) GMR (90% CIs) for midazolam was 0.734 (0.647-0.832). When co‐administered with cenobamate 200 mg/day, AUC0-last GMRs (90% CI) for midazolam, bupropion, S‐warfarin, and omeprazole were 0.277 (0.238-0.323), 0.615 (0.522-0.724), 1.14 (1.10-1.18), and 2.07 (1.44-2.98), respectively. Co‐administration of cenobamate with midazolam and bupropion probes led to values that were outside and below the no effect boundary, indicating that cenobamate induces the CYP3A4/5 and CYP2B6 enzymes. Co‐administration of cenobamate led to omeprazole values which were outside and above the no‐effect boundary, but with high variability, suggesting that cenobamate may moderately inhibit CYP2C19 activity. No effect on CYP2C9 was observed with the cenobamate and warfarin combination. Co‐administration of cenobamate with these probes drugs was well‐tolerated. In this study, 200 mg/day cenobamate moderately induced CYP3A4/5 (dose‐dependently; 100 mg/day was a weak inducer), was a weak inducer of CYP2B6, moderately inhibited CYP2C19, and had a negligible effect on CYP2C9.